1970
DOI: 10.2307/3896222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environment on the Metabolism and Germination of Crested Wheatgrass Seeds

Abstract: Highlight Seeds of crested wheatgrass (Agropyron desertorum [Fisch. ex Link] Schult.), planted at a depth of 1 inch, germinated well because of relatively constant and favorable moisture conditions. These seeds rapidly synthesized hexose phosphate, uridine diphosphate hexose, nicotinamide adenine dinucleotide, adenosine diphosphate, adenosine triphosphate, and other phosphate esters. Synthesis began 2 to 4 weeks before germination was observed. In contrast, seeds on the soil surface failed to germinate because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
3

Year Published

1971
1971
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
1
12
0
3
Order By: Relevance
“…After periods of severe drought, crested wheatgrass seeds resume synthesis of both ATP (19) and a-amylase (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After periods of severe drought, crested wheatgrass seeds resume synthesis of both ATP (19) and a-amylase (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Crested wheatgrass, the test species, is adapted for germination and establishment on semiarid lands and is often exposed to severe drought and fluctuating moisture conditions (19).…”
mentioning
confidence: 99%
“…Seeds which remained ungerminated on the control treatment 3 months after sowing in summer had a mean laboratory germination of 15%, which indicated that "weathering" greatly reduced viability (Wilson et al, 1970). Table 2 shows that percentage radicleentry was higher on the winter control than on the spring or summer control, due most likely to low strength and moisture tension of the soil surface in winter (Fig.…”
Section: Seeds Taken By Antsmentioning
confidence: 97%
“…To increase productivity on these areas it would be necessary to establish improved perennial pastures by aerial methods. However, establishment of perennial pasture species from surface-sowing has been disappointing (Campbell, 1968;Nelson et al, 1970;Dowling et al, 1971). Attention has been drawn to the dearth of information explaining the reasons for such disappointing results (Cullen, 1965;McWilliam et al, 1970;Wilson et al, 1970).…”
mentioning
confidence: 99%
“…Seeds begin metabolism during the early stages of imbibition (Mayer and Poljakoff-Mayber 1982). Wilson et al ( 1970) measured the synthesis of phosphate esters in crested wheatgrass (Agropyron desertorum) seeds at various intervals after planting to evaluate the sensitivity of seeds to environmental changes and their readiness to germinate. Marked increases in ester production were measurable after 4.3 mm of rainfall.…”
Section: °C Soil Surface Temperaturementioning
confidence: 99%